A Review of Palliative Care Service Delivery Models and Patient Outcomes for Adults with Cancer in Selected East and Southeast Asian Countries - Tseng, Chun-Yi; Calanzani , Natalia (International Journal of Medical Students, 2023)
Cancer is one of the key leading causes of deaths worldwide, with a disproportionately high burden in Asia in terms of incidence and mortality. Guidelines and recommendations published by the World Health Organization (WHO) state palliative care as an essential service for patients with cancer and other chronic diseases. Currently, there is extensive evidence regarding different models of palliative care delivery. However, development of palliative care services remains fragmented in Asia, and more research is needed to synthesize available models of care in this region and provide the latest evidence-based information for healthcare providers. This narrative review identified 11 peer-reviewed studies published after 2017 that reported both on models of palliative care service delivery and outcomes for adult patients with cancer in selected East and Southeast Asian countries. This review is beneficial by providing a detailed summary of the models of care adopted by these countries, and their impact on patient outcomes. It is hoped that the evidence will also generate momentum for continued conversation around palliative care development in Asia.